Behavioural responses of zebrafish larvae to acute ethosuximide exposure. Issue 6 (September 2017) - Ji, Yongxia; Lin, Jia; Peng, Xiaolan; Liu, Xiuyun; Li, Fei; Zhang, Yinglan; Guo, Ning; Li, Qiang
Abstract : The anticonvulsant drug ethosuximide has shown diverse anxiety-related activity in rodents, but research in zebrafish is limited. To evaluate the effects of acute ethosuximide exposure on locomotor activity and anxiety-related thigmotaxis behaviours of zebrafish larvae, the activity of AB strain zebrafish larvae at 5 and 7 days postfertilization (dpf) was analysed under normal constant illumination and stressful light–dark transitions. Under constant illumination, ethosuximide at concentrations of 2, 5 and 10 mmol/l increased the distances travelled and intensified locomotor responses to a novel environment. In addition, 40 mmol/l ethosuximide decreased the travel distance and attenuated the locomotor response to darkness. The effects were age related. Under constant illumination, ethosuximide at 40 mmol/l reduced thigmotaxis behaviours in larvae at both ages. Under the light–dark transition, 5 mmol/l ethosuximide reduced thigmotaxis behaviours in 7-dpf larvae. We concluded that under constant lighting, ethosuximide at low concentrations (2, 5 and 10 mmol/l) stimulated the locomotor activity of zebrafish larvae, whereas a high concentration (40 mmol/l) inhibited the activity. Ethosuximide at a low concentration (5 mmol/l) showed anxiolytic effects during the stressful light–dark transition in 7-dpf larvae. The effects of ethosuximide were age and concentration related.